THE INFLUENCE OF MIND MAPPING ON STUDENT LEARNING OUTCOMES ON MOTOR FUEL CONCEPT MATERIALS SUBJECTS OF ENERGY CONVERSION MACHINE CLASS X SMK COUNTRY 1 BUNTOK ACADEMIC YEAR 2016/2017 - Hermanto (Jurusan Pendidikan Teknologi Dan Kejuruan, 2018)
The purpose of this study is to determine the effect of the use of mind mapping learning model on student learning outcomes for the Concept Motor Burning Subject. In the subjects of Energy Conversion Machine, one of the problems is that wanting to be repaired by the researcher which is for the Concept Motor Burning Subject. The previous student learning outcomes are mostly under at the Minimization Completeness Criteria (KKM). Some problems in learning are only using the lecture method thus have been active as teacher role while students tend to be passive. Students are pessimistic in the learning then learning process becomes ineffective. This research type is True Experimental Design Type using Pretest-Posttest Control Group Design. The subjects of this study are students of class X TSM and X TKR SMKN 1 Buntok with population of 50 students. The study took a sample of 50 students, 25 TSM class and 25 TKR SMKN 1 Buntok class in which there is experiment class and control class chosen at random. The experimental class uses the Mind Mapping learning model and the control class using conventional lecture learning model. In this study instrument has used the form of multiple choice for cognitive and questionnaire attitude to be affective to collect student learning outcomes. Result of research and analysis of normality test data were getting the pretest and posttest data of normal distribution that hypothesis test used t test obtaining tct = 2.057> ttable = 2.011 (2.057> 2.011) because tcount = 2.057. it was bigger than ttable = 2.011. This means that H0 is rejected and H1 accepted and indicating that there are differences in the effect of student learning outcomes taught in the experiment class and control class with the Motor Fuel Concept Subject. Finally it can be concluded that the learning outcomes of students using Mind Mapping learning model is more significant than the students trained using the conventional learning model on the Concept Motor Burning Subject at SMKN 1 Buntok.